The Survival and Prognostic Factors of Supratentorial Cortical Ependymomas: A Retrospective Cohort Study and Literature-Based Analysis - Wang, Qiguang; Cheng, Jian; Li, Jiuhong; Zhang, Si; Liu, Wenke; Ju, Yan; Hui, Xuhui (Frontiers in Oncology, 2020)
Aim Survival rates and prognostic factors of cortical ependymomas (CEs) remain elusive. This study aimed to perform a comprehensive analysis of prognostic factors, treatment, and outcomes for patients with CEs based on institutional and literature case series. Materials and Methods Thirty patients with CEs from our department were included in this study. Furthermore, a systemic review of the literature yielded an additional 106 patients with CEs. Clinical data including patient age, sex, symptoms, tumor location, World Health Organization (WHO) grade, extent of surgery, radiation, recurrence, and survival were recorded and statistically analyzed. Results From January 2009 to October 2019, 30 (4.2%) cases were diagnosed as CEs in our department. These series consisted of 19 males and 11 females, 10 continuous patients after 2017 screened for C11orf95-RELA fusion, and 9 patients (90%) were RELA fusion positive. During the follow-up period, nine (30%) patients depicted tumor recurrence or progression; four (13.3%) patients died of tumor progression. The literature review yielded 106 CE cases, with additional 30 cases of our own collected for further analysis. Of these 136 cases, the frontal lobe (40%) was the most common location, and the average age was 22.6 ± 17.6 years. Anaplastic histology/WHO grade III tumors were identified in 68 (50%) patients. Statistically analysis demonstrated that extent of surgery and WHO tumor grade were significant prognostic factors in Kaplan–Meier log-rank testing and Cox proportional hazards models. Gross total resection (GTR) predicted longer progression-free survival (PFS) [P = 0.013, hazard ratio (HR) = 3.012, 95% confidence interval (CI) = 1.257–7.213] and overall survival (OS) (P = 0.003, HR = 5.322, 95% CI = 1.751–16.178). WHO grade III tumors had worse PFS (P = 0.002, HR = 5.17, 95% CI = 1.804–14.816) and OS (P = 0.025, HR = 5.640, 95% CI = 1.248–25.495). Conclusion CEs accounted for only 3.5 to 5.7% of ependymomas, with seizures the most common symptom and the frontal lobe the most frequent location. CEs may have higher rate of RELA fusions, but generally favorable prognosis. The extent of surgery and WHO tumor grade were significant prognostic factors for PFS and OS in multivariate analysis. GTTR or WHO grade II tumors had better overall outcome in patients with CEs.